Experiential Avoidance and Psychological Acceptance Processes in the Psychological Recovery from Enduring Mental Illness - Siqueira , Vinicius R. (International Journal of Psychosocial Rehabilitation, 2014)
Objective: The concept of recovery has been generating significant interest in mental health contexts, as has the behavioral change ap- proach of acceptance and commitment therapy (ACT) within clinical psychotherapy contexts. This exploratory study sought to examine whether a person in psychological recovery from mental illness would describe the use of psychological acceptance and experiential avoidance, two core concepts of ACT. Methods: Forty-five published narratives of people in recovery were content analyzed seeking to investigate the role and frequency of experiential avoidance and psychological acceptance given by those narrating their recovery journey. Results: There was a presence of psychological acceptance in narratives of people self reporting success in their recovery journey sug- gestive that it will correlate with positive developments in ones journey of recovery. Conversely the role and frequency of experiential avoidance in these narratives may be associated with less progress in psychological recovery from mental illness. Conclusion: This study showed preliminary data of the presence of experiential avoidance and psychological acceptance in narratives of people with enduring mental illness, indicating that psychological acceptance may play a positive role in the recovery from mental ill- ness.